Physiological responses during interval training with different intensities and duration of exercise - Zuniga, J. M.; Berg, K.; Noble, J.; Harder, J.; Chaffin, M. E.; Hanumanthu, V. S. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to compare 4 interval training (IT) sessions with different intensities and durations of exercise to determine the effect on mean VO2, total VO2, and duration of exertion =95% maximum power output (MPO), and the effects on biomarkers of fatigue such as blood-lactate concentration (BLC) and rating of perceived exertion. The subjects were 12 recreationally competitive male (n = 7, mean ± SD age = 26.2 ± 3.9 years) and female (n = 5, mean ± SD age = 27.6 ± 4.3 years) triathletes. These subjects performed 4 IT sessions on a cycle ergometer varying in intensity (90 and 100% MPO) and duration of exercise (30 seconds and 3 minutes). This study revealed that IT using 30-second duration intervals (30-30 seconds) allows the athlete to perform a longer session, with a higher total and mean VO2 HR and lower BLC than 3-minute durations. Similarly, submaximal exertion at 90% of MPO also allows performing longer sessions with a higher total VO2 than 100% intensity. Thus, the results of the present study suggested that to increase the total time at high intensity of exercise and total VO2 of a single exercise session performed by the athlete, IT protocols of short durations (i.e., 30 seconds) and submaximal intensities (i.e., 90% MPO) should be selected. Furthermore, performing short-duration intervals may allow the athlete to complete a longer IT session with greater metabolic demands (VO2) and lower BLC than longer (i.e., 3 minutes) intervals.